Information technology capabilities towards SMES innovation capabilities through knowledge management: The review analysis - Ahamat, Amiruddin; Naser Alteneiji, Talal Mohammed Ahmed; Ahmad Murad, Murzidah; Halawani, Esam Adel (Penerbit UTeM, 2024)
Purpose: This study aims to explore the role of information technology (IT) competencies in enhancing innovation capabilities within small and medium enterprises (SMEs) in the service sector of the United Arab Emirates (UAE). Design/methodology/approach: The study is designed as a literature review analysis, which involves systematically collecting, reviewing, and synthesizing existing research and theoretical perspectives on the relationship between IT capabilities, knowledge management (KM), and innovation in SMEs. Findings: The findings indicate that IT competencies, particularly IT infrastructure, IT integration, and IT knowledge, significantly influence innovation capabilities in SMEs. Furthermore, the study confirms that knowledge management mediates the relationship between IT competencies and innovation capabilities, highlighting the importance of effectively managing knowledge assets to leverage IT investments for innovation. Research limitations/implications: The study is limited to SMEs in the service sector within the UAE, which may affect the generalizability of the findings to other sectors or regions. Future research could expand the scope to include different sectors and geographic areas to validate and extend the findings. Practical implications: The study underscores the critical role of IT competencies in driving organizational innovation and suggests that SMEs should prioritize investments in IT infrastructure, integration, and knowledge. Additionally, it highlights the importance of adopting effective knowledge management strategies to maximize the benefits of IT investments and foster innovation. Originality/value: This study contributes to the understanding of how IT competencies enhance innovation capabilities in SMEs, particularly in the context of the UAE's service sector.